Exploring the Cognitive and Social Benefits of Reading Skills Among 6th Semester Students of English Education at Hamzanwadi University - Usuluddin Usuluddin; Astrid Dwimaulani; Nisa Seftiana; Laila Wati (Publikasi Indonesia, 2025)
Reading is one of the four language skills that are very important to master, as it contributes not only to academic success but also to cognitive and social development. This study aims to explore the cognitive and social benefits obtained from reading skills among 6th semester students of the English Language Education Program at Hamzanwadi University. Using qualitative descriptive methods, data was collected through questionnaires (closed-ended and open-ended questions) validated by linguists and semi-structured interviews that had been tested for reliability. The research population was all semester 6 students of the English Education Study Program, Hamzanwadi University, which amounted to 120 students, with a sample of 12 students selected using purposive sampling techniques based on consistent reading activities. Data analysis uses thematic analysis through coding, categorization, and theme development stages. The findings show four main themes: (1) the improvement of critical thinking skills, (2) the development of vocabulary and language structure, (3) the improvement of social skills and participation, and (4) the formation of independent learning habits. This study concludes that reading skills significantly promote cognitive enrichment through improved analytical and linguistic skills, as well as improving students' ability to interact meaningfully with others in and out of the classroom. The implications of the study point to the need for the development of a more comprehensive reading curriculum and learning strategies that emphasize cognitive and social aspects in English language education.